Comparação dos cuidados de saúde oral numa população com trissomia 21 e seus irmãos - Viviana Macho (2008)
Background: The purpose of this study was to compare oral health care (age of first dental visit, regularity and reason of visits, treatment of last visit) in a population with trisomy 21 and their siblings. Methods: The sample was composed by 152 (63%) children with Trisomy 21 and 88 (37%) siblings of these children. They were observed in a pedodontics consultation, specifically created for this purpose, in the facilities of the faculty of Dental Medicine of the Universities of Porto and Lisbon. The information was obtained through a questionnaire made specifically for this purpose for parents or legal guardians. The analysis was made by using the statistical analysis program SPSS® v.14.0. A level of significance of 0,05 were considered. Results: The median value of first dental visit children with Trisomy 21 was 3 years of age and their siblings was 5 years of age (p< 0.001). We verified that 50% of the participants visit their dentist at least once a year, not existing any difference between both groups (p=0.224). The main reason why children go to the dentist was to have a check-up (75%), being this the most frequent answer in both groups. The last treatments were preformed dental fillings in 24 children (9 children with T21 and 15 siblings), verifying a significant statistical difference (p=0.001). During the last visit, 5 children had endodontic treatment, all being included in the group of siblings, verifying a significant statistical difference. Conclusions: Children with T21 visit the dentist at an earlier age compared to their siblings. There is no difference between both groups when comparing the number and regularity of dental visits. Children with T21 have less cavity treatments. Keywords: Trisomy 21, Down syndrome, oral health care, dental treatment.